Unveiling carbapenem resistance: mechanism and therapeutic strategies - R., Thanushree D.; H., Fiza S.; A., Sanjana; U., Mounashree (International Journal of Research in Medical Sciences, 2025)
This review provides an overview of the carbapenem resistance, its underlying causing microbes, its mechanism of transmission, risk factors, and its treatment options and challenges. Carbapenem resistance in Gram-negative organisms such as E. coli and K. pneumoniae, S. pneumoniae, S. aureus, P. aeruginosa, and A. baumannii are major causing microbes. Here we discuss the importance of infection control measures to mitigate the spread of resistance and urgent need for novel therapeutic strategy to defeat this resistance. Furthermore, we explore innovative approaches including the development of new antibiotics, combination therapies and the repurposing of existing drugs to combat carbapenem-resistance strains. Understanding the molecular basis of carbapenem resistance is crucial for developing effective treatment strategies and controlling the spread of antibiotic-resistant bacteria.